A Pragmatic Analysis of Dialogue Between Two Characters in the Old Man and the Sea Based on the Cooperative Principle - Rasheed, Mohammed Hameed (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
This study conducts a pragmatic analysis of the dialogue between characters in Ernest Hemingway's